Small choroidal melanoma and pseudomelanomas: methods of differential diagnostics (literature review). Part 3 - E. B. Myakoshina (Российский офтальмологический журнал)
The third part of literature review (see first part in ROJ 2019; 12 (4): 99–108, second part in ROJ 2020; 13 (2): 88–98) discusses the features characteristic of small uveal melanoma and pseudomelanomas (choroidal nevus, circumscribed choroidal hemangioma, melanocytoma, choroidal metastatic carcinoma, congenital hypertrophy of retinal pigment epithelium, late-stage age-related macular degeneration, focal retinochoroiditis, organized subretinal hemorrhage, retinal hemangioma) which were revealed by optical coherence tomography and optical coherence tomography-angiography. The need for further comparative studies aimed at defining differential diagnostic is emphasized.